Optical Fibre Sensors and Methods - Munjal, Manish; Grewal, Amit; Yadav, Harsh (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2014)
This research paper is about a multi-mode fibre optic sensor for optically sensing a physical perturbation including a multi- mode optical fibre segment which accepts coherent monochromatic radiation from a suitable source. As the radiation is propagated in the fibre, the various modes form a complex interference pattern which changes in response to a physical perturbation of the fibre. A detector provides an output signal to a signal processor which analyzes the signal as a function of the change in intensity to provide an information signal functionally related to the perturbation.